Mercy Watson goes for a ride - DiCamillo, Kate.; Van Dusen, Chris (Somerville, Mass. : Candlewick Press, 2009)
Mr. Watson's usual Saturday drive in his Cadillac with his favorite pig, Mercy, turns into an adventure when an unexpected passenger shows up in the back seat and Mercy finds herself behind the wheel.
Booklist
Notable/Best Books (A.L.A.)
School Library Journal
Booklist, May 2006
Kirkus Review, May 2006
Notable/Best Books (A.L.A.), January 2007
Keywords: Automobile driving -- Juvenile fiction; Swine -- Juvenile fiction; Watson, Mercy (Fictitious character) -- Juvenile fiction; Automobile driving -- Fiction; Humorous stories; Pigs -- Fiction; Watson, Mercy (Fictitious character) -- Fiction; Automobile drivers -- Fiction; Humorous fiction; Pigs -- Fiction; Watson, Mercy (Fictional character) -- Fiction; Humorous fiction